2022
DOI: 10.1002/hbm.25837
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: Performance metric evaluation in brain‐age prediction

Abstract: Estimating age based on neuroimaging-derived data has become a popular approach to developing markers for brain integrity and health. While a variety of machinelearning algorithms can provide accurate predictions of age based on brain characteristics, there is significant variation in model accuracy reported across studies. We predicted age in two population-based datasets, and assessed the effects of age range, sample size and age-bias correction on the model performance metrics Pearson's correlation coeffici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 94 publications
(249 reference statements)
5
76
0
Order By: Relevance
“…Each algorithm was trained using grid search to find the best parameters that give the highest accuracy. The performance of each algorithm was quantified by the Pearson’s correlation coefficient (r) and mean absolute error (MAE) between predicted brain age and chronological age [ 6 ]. We also reported weighted MAE for comparison between studies with different sample age ranges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each algorithm was trained using grid search to find the best parameters that give the highest accuracy. The performance of each algorithm was quantified by the Pearson’s correlation coefficient (r) and mean absolute error (MAE) between predicted brain age and chronological age [ 6 ]. We also reported weighted MAE for comparison between studies with different sample age ranges.…”
Section: Methodsmentioning
confidence: 99%
“…The biological age of the brain (“brain age”) is estimated typically by applying a machine learning approach to magnetic resonance imaging (MRI) data to predict chronological age. The difference between an individual’s predicted brain age and actual chronological age is referred to here as brain-predicted age difference (brainPAD) [ 2 , 3 ], which is also known as brain age gap [ 4 , 5 ] or brain age delta [ 6 ]. This metric reflects the deviation from expected age trajectories and is often used to index brain health [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed lower wMAEs in BASE-II when compared to UK Biobank, suggesting lower model accuracies in BASE-II. Notably, wMAE has been reported to vary as a function of age range, as it does not account for the underlying age distribution (de Lange et al, 2022). Therefore, we additionally matched UK Biobank to BASE-II participants by chronological age and sex using R package MatchIt (Ho et al, 2011), and recalculated prediction accuracies for the resulting UK Biobank subset (for details see section "Comparison of Age Prediction Accuracies in BASE-II and UK Biobank" in Supplementary Material A).…”
Section: Prediction Accuraciesmentioning
confidence: 99%
“…Most people, who showed advanced age in one measure, also did so in other measures. Furthermore, as argued elsewhere (de Lange et al, 2022), performance metrics such as MAE are sample-specific (i.e., they cannot easily be compared across studies) and should be considered in combination with other metrics such as correlation coefficients. For example and similar to our study, large increases in MAE have been reported despite acceptable correlations (r > 0.5) between chronological and predicted age, especially in situations where the age range of the testing sample was very narrow and different to that of the training sample (de Lange et al, 2022).…”
Section: Discussionmentioning
confidence: 99%